2019
DOI: 10.1080/20961790.2019.1592314
|View full text |Cite
|
Sign up to set email alerts
|

Neck-MRI experience for investigation of survived strangulation victims

Abstract: For the medicolegal evaluation of victims of survived strangulation, a neck-magnetic resonance imaging (MRI) can be performed for assessing lesions in the inner soft tissues (fat, muscles or lymph nodes, for example). In our institute, such MRI examinations have been performed for a test period of 4 years with the aim of evaluating the use of this tool by forensic pathologists and identifying medicolegal indicators for the performance of neck-MRI in surviving victims of strangulation. We retrospectively review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Four of the articles identified that survivors of NFS were referred for medical imaging as part of police investigation or by other protective organisations such as child/adult protective services 17 21–23. The remaining three articles did not specify a referral pathway 24–26…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of the articles identified that survivors of NFS were referred for medical imaging as part of police investigation or by other protective organisations such as child/adult protective services 17 21–23. The remaining three articles did not specify a referral pathway 24–26…”
Section: Resultsmentioning
confidence: 99%
“…Radiological imaging, including MRI and CT, was used in six studies. Of these, four studies used MRI,17 21 22 25 and one study used CT or MRI 26. Separately, one article did not use radiological imaging to investigate strangulation injuries, instead using alternative light sources (ALS) 23.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To exclude life-threatening complications such as carotid dissections [5], computed tomography (CT) with angiography is often applied in severe cases of NFS. The application of magnetic resonance imaging has been investigated with mixed results [6][7][8][9]. Overall, the need for sharply defined findings for the evaluation of NFS remains.…”
Section: Introductionmentioning
confidence: 99%